EXPLORING VARIOUS STORYTELLING METHODS IN JAPANESE-STYLE ROLE-PLAYING GAMES (JRPG) - Sugiarto; Santi Widiastuti (STEKOM PRESS, 2021)
Main Objective: This study reports an experiment to explore differences in player feedback caused by different storytelling methods of Japanese-style Role-playing Games (JRPG). Background problem: Narration is considered the soul of JRPG, and is a vital and irreplaceable role. Different ways of telling stories can bring different experience effects even though the essence of the story is the same. Stories are presented directly to players in dialogue form, much like a visual interactive novel. Non-linear storytelling can break down important parts and allow players to explore freely. Players can collect clues to get to the main plot. Also, most JRPGs use short films and sound effects to create a cinematic experience. Novelty: Based on all studies of game storytelling (linear and nonlinear), this study will compare player feedback on different storytelling methods to see which narrative can provide a better player experience. Research Method: Researchers categorize these three narratives as Visual Novels, Environmental Narratives, Visuals, Sounds, and Dialogues. This experiment combined all three of Caught in Trap's in-game narratives to investigate player preferences. Data was collected through questionnaires and interviews with 21 players who were invited to play the game. Finding/Result: The research results show that the three ways of storytelling enrich the expression of game narratives. Both linear and nonlinear narratives have their advantages and disadvantages, and the best way to engage players is to interweave both narratives in the game. Conclusion: The experimental results show that the interweaving of three ways of storytelling can enrich the narrative form of games and guide game designers in improving game plots to engage players in JRPGs. Keywords: Storytelling-Method, JPRG, Game of Three Pillars